A porous copper based on selective dezincing of brass by vapor phase and a preparation method thereof

CN122918376APending Publication Date: 2026-10-16ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611012341.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]本发明的目的在于克服现有技术存在的多孔铜制造工艺复杂、生产效率低下、污染环境以及成本高昂的问题,提供一种基于黄铜气相选择性脱锌的多孔铜及其制备方法,提供了成本适中、无污染、生产效率高的多孔铜制造方法,孔隙率为40%~70%,电导率≥85%IACS,抗拉强度≥120MPa,比表面积≥10m2/g

Benefits of technology

1.绿色环保:制造全程不涉及强酸、碱,无废水排放,符合高端制造环保要求。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of porous copper based on brass gas phase selective dezincification and preparation method thereof, comprising the following steps: raw material selection: select brass foil as raw material;Surface pretreatment: the brass foil is placed in alkaline oil removal liquid and is soaked, after being washed with deionized water, then placed in dilute hydrochloric acid and is cleaned, remove surface oxide layer, after drying, obtain pretreated brass foil;Segmented gas phase selective dezincification: the pretreated brass foil is placed in tube furnace that is vacuumed to 10 ‑2 ~10 ‑3 Pa, nitrogen is passed to furnace pressure to normal pressure, then carry out segmented temperature control dezincification treatment, obtain porous copper: wherein, segmented temperature control dezincification treatment includes pre-dezincification stage and depth dezincification stage.The application provides a porous copper manufacturing method with moderate cost, no pollution and high production efficiency, porosity is 40%~70%, electrical conductivity is ≥85%IACS, tensile strength is ≥120MPa, specific surface area is ≥10m 2 / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous metal materials technology, and more specifically, to a porous copper based on selective dezincification of brass in the vapor phase and its preparation method, which is suitable for the manufacture of long-life and high-safety lithium batteries. Background Technology

[0002] In recent years, the rapid development of artificial intelligence, electric vehicles, and clean energy technologies has greatly increased the demand for functional metal structural materials. Porous metal materials, as the most economical and efficient, have been widely used in high-capacity batteries, thermal insulation, sound insulation and vibration damping, and catalyst manufacturing, with annual usage reaching 300,000 tons. Porous copper alone has a global annual consumption of approximately 60,000 tons. Currently, the preparation methods for porous metal materials are mainly based on powder metallurgy, which suffers from drawbacks such as complex processes, low efficiency, and environmental pollution, greatly limiting the production and widespread application of porous metal materials. Summary of the Invention

[0003] The purpose of this invention is to overcome the problems of complex manufacturing processes, low production efficiency, environmental pollution, and high costs associated with existing porous copper manufacturing technologies. This invention provides a porous copper based on selective vapor-phase zinc removal from brass and its preparation method. It offers a cost-effective, pollution-free, and highly efficient method for manufacturing porous copper with a porosity of 40%–70%, electrical conductivity ≥85% IACS, tensile strength ≥120 MPa, and specific surface area ≥10 m². 2 / g.

[0004] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing porous copper based on selective dezincification of brass in the vapor phase includes the following steps: (1) Raw material selection: Brass foil was selected as the raw material; (2) Surface pretreatment: The brass foil is immersed in an alkaline degreasing solution, rinsed with deionized water, and then cleaned in dilute hydrochloric acid to remove the surface oxide layer. After drying, the pretreated brass foil is obtained. (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10 -3 In a tubular furnace at pressure Pa, nitrogen gas is introduced until the furnace pressure reaches atmospheric pressure, and then a segmented temperature-controlled zinc stripping process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage; the pre-dezincification stage involves heating to 200-300℃ and holding for 20-40 minutes; the deep dezincification stage involves heating to 350-500℃ and holding for 30-90 minutes.

[0005] Optionally, in step (1), the zinc content in the brass foil is 15wt% to 30wt%, and the impurity content is not higher than 0.5wt%.

[0006] Optionally, in step (1), the thickness of the brass foil is 20 to 100 μm.

[0007] Optionally, in step (2), the alkaline degreasing solution has a pH of 10 to 11.

[0008] Optionally, in step (2), the soaking temperature is 50-70°C and the soaking time is 3-10 min.

[0009] Optionally, in step (2), the concentration of the dilute hydrochloric acid is 3% to 10%.

[0010] Optionally, in step (2), the cleaning time is 10 to 60 seconds.

[0011] Optionally, in step (2), the drying temperature is 50~80℃.

[0012] Optionally, in step (3), during the segmented temperature-controlled dezincification process, the zinc partial pressure is controlled to be 0.01 to 1 kPa.

[0013] Optionally, in step (3), the heating rate of the pre-dezincification stage is 30~50℃ / min; the heating rate of the deep dezincification stage is 60~120℃ / min.

[0014] Optionally, in step (3), the nitrogen purity is ≥99.99%.

[0015] The present invention also discloses a porous copper prepared by the preparation method described above.

[0016] Optionally, the residual zinc content in the porous copper is 0.1 wt% to 1 wt%. Optionally, the porous copper has a porosity of 40%–70%, an electrical conductivity ≥85% IACS, a tensile strength ≥120 MPa, and a specific surface area ≥10 m². 2 / g.

[0017] Implementing the embodiments of the present invention will have the following beneficial effects: 1. Green and environmentally friendly: The entire manufacturing process does not involve strong acids or alkalis and there is no wastewater discharge, which meets the environmental protection requirements of high-end manufacturing.

[0018] 2. Controllable pore structure: Segmented temperature and zinc partial pressure are synergistically controlled, and pore size, porosity, and residual zinc are precisely controllable.

[0019] 3. Excellent conductivity and strength: The trace amount of residual zinc solid solution strengthening also results in high conductivity.

[0020] 4. Low raw material cost: General-purpose brass foil is widely available and can be produced continuously.

[0021] 5. Significantly improves lithium battery life and safety: Used in the negative electrode of lithium batteries, it significantly suppresses lithium dendrites.

[0022] 6. The preparation method of this invention has moderate cost, no pollution, and high production efficiency. The porous copper obtained has a residual zinc content of 0.1wt% to 1wt%, a porosity of 40% to 70%, an electrical conductivity ≥85% IACS, a tensile strength ≥120MPa, and a specific surface area ≥10m². 2 / g. Detailed Implementation

[0023] The present invention will be further described below with reference to specific embodiments, but this does not limit the present invention in any way.

[0024] This invention discloses a method for preparing porous copper based on selective dezincification of brass in the vapor phase, comprising the following steps: (1) Raw material selection: Brass foil was selected as the raw material; (2) Surface pretreatment: The brass foil is immersed in an alkaline degreasing solution, rinsed with deionized water, and then cleaned in dilute hydrochloric acid to remove the surface oxide layer. After drying, the pretreated brass foil is obtained. (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10 -3 In a tubular furnace of Pa, nitrogen gas is introduced until the furnace pressure reaches atmospheric pressure, and then a segmented temperature-controlled dezincification process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage. In the pre-dezincification stage, the temperature is raised to 200-300℃ and held for 20-40 minutes to allow the surface zinc atoms to initially diffuse and volatilize. In the deep dezincification stage, the temperature is raised to 350-500℃ and held for 30-90 minutes to achieve deep selective volatilization of zinc atoms.

[0025] In one specific embodiment, in step (1), the zinc content in the brass foil is 15wt% to 30wt%, and the impurity content is not higher than 0.5wt%.

[0026] In one specific embodiment, in step (1), the thickness of the brass foil is 20 to 100 μm.

[0027] In one specific embodiment, in step (1), the brass foil is of grade H68, H70 or H75.

[0028] In one specific embodiment, in step (2), the alkaline degreasing solution has a pH of 10 to 11.

[0029] In one specific embodiment, in step (2), the soaking temperature is 50-70°C and the soaking time is 3-10 min.

[0030] In one specific embodiment, in step (2), the concentration of dilute hydrochloric acid is 3% to 10%.

[0031] In one specific embodiment, the cleaning time in step (2) is 10 to 60 seconds.

[0032] In one specific embodiment, in step (2), the drying temperature is 50~80℃.

[0033] In one specific embodiment, in step (3), during the segmented temperature-controlled zinc removal process, the zinc partial pressure is controlled to be 0.01 to 1 kPa by matching the gas flow rate with the furnace pressure throughout the process, so as to avoid oxidation of the copper matrix and coarsening of the grains.

[0034] In one specific embodiment, in step (3), the heating rate of the pre-dezincification stage is 30~50℃ / min. The heating rate of the deep dezincification stage is 60~120℃ / min.

[0035] In one specific embodiment, in step (3), the nitrogen purity is ≥99.99%.

[0036] The present invention also discloses a porous copper prepared by the preparation method described above.

[0037] In one specific embodiment, the residual zinc content in the porous copper is 0.1wt% to 1wt%.

[0038] In one specific embodiment, the porous copper has a porosity of 40%–70%, an electrical conductivity ≥85% IACS, a tensile strength ≥120 MPa, and a specific surface area ≥10 m². 2 / g.

[0039] The following are specific embodiments. Example 1 The porous copper preparation method based on selective dezincification of brass in the vapor phase of this embodiment includes the following steps: (1) Raw material selection: H70 brass foil with a thickness of 50μm was selected as the raw material.

[0040] (2) Surface pretreatment: The brass foil was placed in an alkaline degreasing solution with pH 10 and soaked at 60°C for 5 minutes. After rinsing with deionized water, it was then placed in a 5% dilute hydrochloric acid solution for 30 seconds to remove the surface oxide layer. The brass foil was then dried at 80°C to obtain the pretreated brass foil.

[0041] (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10-3 In a tubular furnace at pressure Pa, nitrogen gas with a purity ≥99.99% is introduced until the furnace pressure reaches atmospheric pressure. Then, a segmented temperature-controlled dezincification process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage. The pre-dezincification stage involves heating to 250℃ at a rate of 30℃ / min and holding for 30 minutes; then heating to 420℃ at a rate of 60℃ / min and holding for 60 minutes. Throughout the segmented temperature-controlled dezincification process, the zinc partial pressure is controlled at 0.2 kPa by matching the gas flow rate with the furnace pressure.

[0042] The porous copper prepared in this embodiment has a residual zinc content of 0.35 wt%, a porosity of 58%, an electrical conductivity of 91% IACS, a tensile strength of 146 MPa, and a specific surface area of ​​12.6 m². 2 / g.

[0043] Example 2 The porous copper preparation method based on selective dezincification of brass in the vapor phase of this embodiment includes the following steps: (1) Raw material selection: H68 brass foil with a thickness of 30μm was selected as the raw material.

[0044] (2) Surface pretreatment: The brass foil was placed in an alkaline degreasing solution with pH 10 and soaked at 60°C for 5 minutes. After rinsing with deionized water, it was then placed in a 5% dilute hydrochloric acid solution for 30 seconds to remove the surface oxide layer. The brass foil was then dried at 80°C to obtain the pretreated brass foil.

[0045] (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10 -3 In a tubular furnace at pressure Pa, nitrogen gas with a purity ≥99.99% is introduced until the furnace pressure reaches atmospheric pressure. Then, a segmented temperature-controlled dezincification process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage. The pre-dezincification stage involves heating to 220℃ at a rate of 40℃ / min and holding for 25 minutes; then heating to 380℃ at a rate of 100℃ / min and holding for 45 minutes. Throughout the segmented temperature-controlled dezincification process, the zinc partial pressure is controlled at 0.01 kPa by matching the gas flow rate with the furnace pressure.

[0046] The porous copper prepared in this embodiment has a residual zinc content of 0.22 wt%, a porosity of 52%, an electrical conductivity of 93% IACS, a tensile strength of 131 MPa, and a specific surface area of ​​12.1 m². 2 / g.

[0047] Example 3 The porous copper preparation method based on selective dezincification of brass in the vapor phase of this embodiment includes the following steps: (1) Raw material selection: H75 brass foil with a thickness of 50μm was selected as the raw material.

[0048] (2) Surface pretreatment: The brass foil was placed in an alkaline degreasing solution with pH 10 and soaked at 60°C for 5 minutes. After rinsing with deionized water, it was then placed in a 5% dilute hydrochloric acid solution for 30 seconds to remove the surface oxide layer. The brass foil was then dried at 80°C to obtain the pretreated brass foil.

[0049] (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10 -3 In a tubular furnace at pressure Pa, nitrogen gas with a purity ≥99.99% is introduced until the furnace pressure reaches atmospheric pressure. Then, a segmented temperature-controlled dezincification process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage. The pre-dezincification stage involves heating to 300℃ at a rate of 50℃ / min and holding for 40 minutes; then heating to 500℃ at a rate of 120℃ / min and holding for 90 minutes. Throughout the segmented temperature-controlled dezincification process, the zinc partial pressure is controlled at 0.3 kPa by matching the gas flow rate with the furnace pressure.

[0050] The porous copper prepared in this embodiment has a residual zinc content of 0.5 wt%, a porosity of 70%, an electrical conductivity of 90% IACS, a tensile strength of 160 MPa, and a specific surface area of ​​11.2 m². 2 / g.

[0051] Comparative Example 1 This comparative example uses conventional liquid-phase hydrochloric acid to dezincify porous copper. H70 brass foil (thickness 50μm) is etched at 50℃ for 30min using HCl with a mass concentration of 37%.

[0052] The porous copper prepared in this comparative example has a residual zinc content of 0.05 wt%, a porosity of 62%, an electrical conductivity of 78% IACS, a tensile strength of 75 MPa, and a specific surface area of ​​5 m². 2 / g.

[0053] Comparative Example 2 This comparative example uses ordinary powder-sintered porous copper. Following the process route of Example 1, 37% HCl was used for etching at 50°C for 30 minutes.

[0054] The porous copper prepared in this comparative example has a porosity of 55%, an electrical conductivity of 58% IACS, a tensile strength of 20 MPa, and a specific surface area of ​​3.5 m². 2 / g.

[0055] Comparative Example 3 This comparative example uses single-temperature vapor-phase dezincification porous copper, following the process route of Example 1, but omitting the deep dezincification stage, and using HCl with a mass concentration of 37% for corrosion at 50°C for 30 minutes.

[0056] The porous copper prepared in this comparative example has a residual zinc content of 2 wt%, a porosity of 41%, an electrical conductivity of 82% IACS, a tensile strength of 110 MPa, and a specific surface area of ​​6 m². 2 / g.

[0057] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A method for preparing porous copper based on selective dezincification of brass in the vapor phase, characterized in that, Includes the following steps: (1) Raw material selection: Brass foil was selected as the raw material; (2) Surface pretreatment: The brass foil is immersed in an alkaline degreasing solution, rinsed with deionized water, and then cleaned in dilute hydrochloric acid to remove the surface oxide layer. After drying, the pretreated brass foil is obtained. (3) Segmented vapor-phase selective zinc removal: The pretreated brass foil is placed in a vacuum chamber at 10°C. -2 ~10 -3 In a tubular furnace at pressure Pa, nitrogen gas is introduced until the furnace pressure reaches atmospheric pressure, and then a segmented temperature-controlled zinc stripping process is performed to obtain porous copper. The segmented temperature-controlled dezincification process includes a pre-dezincification stage and a deep dezincification stage; The pre-dezinc removal stage involves heating to 200–300°C and holding for 20–40 minutes. The deep dezincification stage involves heating to 350–500°C and holding for 30–90 minutes.

2. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (1), the zinc content in the brass foil is 15wt% to 30wt%, and the impurity content is no higher than 0.5wt%.

3. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (1), the thickness of the brass foil is 20 to 100 μm.

4. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (2), the alkaline degreasing solution has a pH of 10-11; The soaking temperature is 50–70°C; the soaking time is 3–10 minutes. The concentration of the dilute hydrochloric acid is 3% to 10%; The cleaning time is 10–60 seconds; The drying temperature is 50~80℃.

5. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (3), during the segmented temperature-controlled zinc removal process, the zinc partial pressure is controlled to be 0.01 to 1 kPa.

6. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (3), the heating rate in the pre-dezincification stage is 30~50℃ / min; the heating rate in the deep dezincification stage is 60~120℃ / min.

7. The method for preparing porous copper based on selective dezincification of brass in the vapor phase according to claim 1, characterized in that, In step (3), the nitrogen purity is ≥99.99%.

8. A porous copper prepared by the preparation method according to any one of claims 1-7.

9. The porous copper according to claim 8, characterized in that, The residual zinc content in the porous copper is 0.1 wt% to 1 wt%. The porous copper has a porosity of 40%–70%, an electrical conductivity ≥85% IACS, a tensile strength ≥120MPa, and a specific surface area ≥10m². 2 / g.